Top management team boundary-spanning leadership: Measurement development and its impact on innovative behavior - Liu, Xuemei; Yu, Yuan; Zhao, Xiuwen; Zhang, Ningjun (Frontiers in Psychology, 2022)
With the advancement of digital economy, organizations around the world need to stretch the boundaries of their strategy, business, and knowledge to gain a competitive advantage and achieve sustainable growth. Although boundary-spanning leadership, with a set of practical tools developed by the Center for Creative Leadership (CCL), has been explored over the past 10 years, the comprehensive understanding of top management team boundary-spanning leadership has still reached no consensus. This research focuses on the concept of top management team boundary-spanning leadership (TMTBSL) and its effect on employees’ innovative behavior. Study 1 comprises the concept of TMTBSL and the measurement of its development. The classical grounded theory was used to analyze biographical texts and in-depth interview data from local Chinese organizations. We developed a 5-dimension scale with14 items for TMTBSL. In Study 2, we empirically examined the impact of TMTBSL on employees’ innovative behavior. The results demonstrate that TMTBSL can promote employee innovative behavior through perceived motivational climate. The theoretical and practical implications are also outlined.